2015
DOI: 10.5152/iao.2015.699
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Risk among Young Personal Listening Device Users: Effects at High-Frequency and Extended High- Frequency Audiogram Thresholds

Abstract: OBJECTIVE:The usage of personal listening devices (PLDs) is associated with risks of hearing loss. The aim of this study is to evaluate the effects of music exposure from these devices on high-frequency hearing thresholds of PLD users. MATERIALS and METHODS:A total of 282 young adults were questioned regarding their listening habits and symptoms associated with PLD listening. Their audiogram thresholds were determined at high (3-8 kHz) frequencies and extended high frequencies (EHFs, 9-16 kHz). The preferred l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 20 publications
3
47
0
5
Order By: Relevance
“…The authors confirmed that four [9,[20][21][22] of the selected studies had "good" quality (scored 7-9). The remaining studies were evaluated as having "fair" quality (score 4-6) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] except for one study with a score of 3, evaluated as having "poor" quality [35]. Thus, 16 articles were included for systematic review and meta-analysis in this study.…”
Section: Selection Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors confirmed that four [9,[20][21][22] of the selected studies had "good" quality (scored 7-9). The remaining studies were evaluated as having "fair" quality (score 4-6) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] except for one study with a score of 3, evaluated as having "poor" quality [35]. Thus, 16 articles were included for systematic review and meta-analysis in this study.…”
Section: Selection Outcomesmentioning
confidence: 99%
“…Sixteen high-quality studies that reported hearing thresholds of PTA (4, 6, and 8 kHz testing frequencies) and amplitudes of the DPOAEs (2, 4, and 6 center frequencies) were pooled for analysis. As mentioned earlier, the studies were divided into two groups to see short-term hearing changes (pre/post-exposure with 24 hours; n = 7) [20,23,25,[27][28][29]32] and long-term hearing changes (PLDs users/non-users; n = 9) [9,21,22,24,26,30,31,33,34]. For short-term hearing changes within 24 h after music exposure [20,23,25,[27][28][29]32], the studies pooled for analysis showed PTA 4, 6, and 8 kHz changes at pre-and post-music exposure (see Figure 2).…”
Section: Meta-analysis Of Music Exposure Effects With Subgroup Analysismentioning
confidence: 99%
“…A study in Malaysia found male students listening to music using PADs at significantly higher volumes compared to female students. [13] Similarly, another study among first-year polytechnic students in Singapore found that male students were more likely to listen to music on PADs at louder volumes than female students. [25]…”
Section: Discussionmentioning
confidence: 99%
“…[7891011] Furthermore, recreational NIHS through PADs has an insidious onset which develops over a prolonged period during which the affected individuals are often unaware of the hearing loss as it initially affects higher frequencies while sparing the speech range. [121314] Although modern PADs and smartphones have features for alerting users when volume threshold of the safety limits is exceeded, it is inadequate for protecting hearing since they can be manually overridden by the listener. [15] Also, the sound pressure delivered to the listener depends on the type of earphone, with expensive isolator-style earphones being more protective but are less commonly used in people with limited economic means.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, 16% of incapacitating and irreversible cases of hearing loss in adults are caused by exposure to occupational noise worldwide (1,2). The effects of noise exposure on the auditory system in working populations have been recognized in several countries (3)(4)(5). In general, prolonged exposure to excessive noise leads to adverse effects on one's performance.…”
Section: Introductionmentioning
confidence: 99%